2004
DOI: 10.1182/blood.v104.11.4079.4079
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Fondaparinux in Medical Patients: A Subgroup Analysis.

Abstract: Aim In the ARTEMIS study fondaparinux 2.5mg reduced the overall incidence of venous thromboembolism (VTE) by 47% in general medical patients when compared to placebo. Our aim was to identify which medical patient populations with an acute medical illness or risk factor for VTE benefited from fondaparinux prophylaxis. Method A total of 849 patients were enrolled in 35 centres in 8 countries. Patients were randomised to receive placebo or fondaparinux 2.5mg subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…[48][49][50] Placebocontrolled trials that included patients over 40 years of age, immobility, and additional VTE risk factors compared placebo groups to the LMWHs enoxaparin 40 mg subcutaneously daily and dalteparin 5000 IU subcutaneously daily, or the pentasaccharide fondaparinux 2.5 mg subcutaneously daily with primary efficacy endpoints that were based mostly on lower extremity venographic or ultrasonographic endpoints. [11][12][13] These trials have shown a 50 to 60% reduction in total VTE with a trend toward a numeric excess in MB events. All of these studies had a 6-to 14-day treatment duration.…”
Section: Medically Illmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] Placebocontrolled trials that included patients over 40 years of age, immobility, and additional VTE risk factors compared placebo groups to the LMWHs enoxaparin 40 mg subcutaneously daily and dalteparin 5000 IU subcutaneously daily, or the pentasaccharide fondaparinux 2.5 mg subcutaneously daily with primary efficacy endpoints that were based mostly on lower extremity venographic or ultrasonographic endpoints. [11][12][13] These trials have shown a 50 to 60% reduction in total VTE with a trend toward a numeric excess in MB events. All of these studies had a 6-to 14-day treatment duration.…”
Section: Medically Illmentioning
confidence: 99%
“…10 The results of older inpatient-based randomized placebo-controlled trials with unfractionated heparin (UFH), low-molecular-weight heparin (LMWH), or pentasaccharide fondaparinux have shown a 50 to 60% reduction of total VTE that included both symptomatic VTE and asymptomatic lower extremity DVT (established by screening venography or ultrasonography) that firmly established the effectiveness and net clinical benefit of short term use of thromboprophylaxis given for a duration of 6 to 14 days. [11][12][13] This recommendation has been supported by antithrombotic guidelines. 14 However, the shortened hospital length-of-stay in the U.S., which now averages 4.5 days, coupled with fewer than 4% of hospitalized medically ill patients in the U.S. receiving postdischarge thromboprophylaxis, has dampened the treatment effects of in-hospital thromboprophylaxs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recommendations are based on the results of trials whose cohorts consisted of heterogeneous groups of medical patients, among which cancer patients were underrepresented (5-15%). [19][20][21][22][23] A recent meta-analysis restricted to the cancer subgroup of the aforementioned studies did not confirm a positive effect of thromboprophylaxis. 24 On the other hand, cancer patients also exhibit an increased bleeding tendency and are considered as a highrisk population for hemorrhages.…”
Section: Suggestionsmentioning
confidence: 99%
“…27 In other words, the action threshold was not limited to a unique cutoff but ranged between the likelihood to prevent VTE or cause bleeding (i.e., gastrointestinal bleeding and/or hemorrhagic stroke). 2,3,28,29 In the present study, NB of our prediction model was compared with default policies of "treat all," which was calculated by assuming that all patients were treated with thromboprophylaxis using LMWH or fondaparinux, and "treat none" which means that NB was zero. Finally, with the aim of supporting GPs in clinical decision-making, we complemented the DCA by proposing a score categorization into four different risk subgroups, using cut-points on the prognostic index determined by Cox's methods.…”
Section: Discussionmentioning
confidence: 99%